Labile Carbon Affects Fecundity of Omodeoscolex divergens and Eudrilus eugeniae under Pure and Mixed Culture Vermicomposting. Issue 1 (2nd January 2020) - Martin, Micah; Eudoxie, Gaius; Gouveia, Gregory
Abstract: Detergent fiber analysis was used to fractionate carbon (C) into hemicellulose (degradable carbon) and cellulose and lignin (recalcitrant carbon) for cattle manure (CM), neem leaves (NL), corn stover (CS), and lawn clipping (LC) to investigate the effects of C quality on vermicomposting. A factorial design having five C sources (CM, CM + NL, CS, CS + NL, and LC) and two earthworm species ( Eudrilus eugeniae (EE) and Omodeoscolex divergens (OD)) was studied under pure and mixed culture vermicomposting. Earthworm fecundity, biomass, and vermicompost quality were measured. The combination of culture and C source was significant ( p  < 0.05) for all fecundity and biomass variables. CM and CM + NL were mainly associated with increased responses. Change in population was > tenfold for EE and OD reared on CM. Percentage change in biomass increased up to 200% for OD and EE when fed CM and CM + NL. Contrastingly, decreases or no changes in fecundity and biomass parameters were associated with CS and CS + NL. The NL combinations resulted in lower responses in fecundity and biomass; however, earthworms favored CM + NL over CS + NL. OD was highest ( p  < 0.05) amongst cultures for LC. The mixed culture response was generally low for parameters measured. Vermicompost C/N ratio decreased from initial carbon source values except for LC. O . divergens vermi-converted carbon sources of varying C quality, producing distinct vermicompost in the process.